Effects of genetic variation and environmental factors on bergenin in Rodgersia sambucifolia Hemsl. (30th January 2020) - Song, Mei-Fang; Zhang, Li-Xia; Zhang, Yue; Guan, Yan-Hong; Li, Hai-Tai; Zhang, Zhong-Lian
Abstract: Ethnopharmacological relevance: Bergenin is a well-known active compound that exhibits antioxidant, antiarrhythmic, hepatoprotective, and anti-inflammatory activities. However, the resource reserve of Rodgersia sambucifolia, one of the main raw materials for extracting bergenin, have sharply declined, and the bergenin content in different germplasms differs vastly, resulting in a serious shortage of the market supply of bergenin. Aim of the study: To investigate the influence of genetic diversity and environmental factors on bergenin content in Rodgersia sambucifolia . Materials and methods: Fifty Rodgersia sambucifolia samples with a growth period of 2–3 years were collected from different areas across China and the bergenin content was determined via HPLC. Meanwhile the total genomic DNA was extracted and ISSR was performed. The bergenin content as measured using HPLC and the environmental data gathered from the meteorological stations and field work were combined and analyzed using correlation tests in XLSTAT 2018 to detect the key factors affecting bergenin content. The genetic UPGMA tree constructed based on genetic distances of the 50 samples and the chemical dendrogram constructed according to the distance between the bergenin content were compared to determine the correlation between genetic and chemical differentiation. Results: Among the 50 individuals, bergenin content varied from 2.83 to 12.54%, with the highest content being 4.43-fold that of the lowest content. The survey of the 50 individuals produced a total of 193 amplified bands, 187 of which were polymorphic (96.89%). In the study, bergenin content was positively correlated with annual mean temperature (AMT) (r = 0.583, P  < 0.0001) and 1–12 month monthly mean temperature (MMT) (P < 0.0001). A comparison of the genetic dendrogram with the AHC dendrogram found no corresponding relationship between them. Mantel correlation analyses also showed that there was no significant correlation between them (r = 0.144). Conclusions: There were large differences in bergenin content among different germplasms that were not correlated with the high genetic variation in Rodgersia sambucifolia but were significantly correlated with environmental factors, such as temperature. This study lays the foundation for subsequent superior germplasm selection and artificial breeding of Rodgersia sambucifolia to improve the bergenin content and meet market demands. Graphical abstract: Image 1